Efficient removal of surface-deposited pseudo-lignin and lignin droplets by isothermal phase separation during hydrolysis. (February 2022) - Wu, Ruijie; Wang, Xiaodi; Zhang, Yongchao; Fu, Yingjuan; Qin, Menghua
Graphical abstract: Highlights: Pre-hydrolysis is considered as a promising technology in the biorefinery process. "Pseudo-lignin" were formed and deposited on biomass surface during pre-hydrolysis. The surface-deposits could be removed efficiently by isothermal phase separation. More sugars were extracted by interrupting the formation of "pseudo-lignin". The efficient removal of surface-deposits improved subsequent enzymatic hydrolysis. Abstract: During the traditional autohydrolysis, formation and deposition of "pseudo-lignin" and lignin droplets on the surface of biomass had a detrimental effect on the subsequent biomass conversion. In this study, isothermal phase separation was introduced into autohydrolysis, and the effects of isothermal phase separation on the dissolution of components and enzymatic hydrolysis of bamboo were studied. The research showed that isothermal phase separation after autohydrolysis without cooling had an effective reduction in the deposition of "pseudo-lignin" and lignin droplets on the residues surface. After isothermal phase separation, the contents of sugar (14.05 g/L) and lignin (6.16 g/L) in pre-hydrolysates increased by 20% and 19% compared with control, respectively. Moreover, the efficient removal of "pseudo-lignin" and lignin droplets from cell wall surface could further promote the biological conversion of pretreated biomass (22% higher than that of control) during the subsequent enzymatic hydrolysis.